Speleothem chronology in Ledyanaya Lenskaya and Botovskaya caves used in publication "Paleoclimate evidence of vulnerable permafrost during times of low sea-ice" By Vaks, A. et al.(2020) - Vaks, A; Mason, A.J.; Breitenbach, S. F. M.; Kononov, A. M.; Osinzev, A. V.; Rosensaft, M.; Borshevsky, A.; Gutareva, O. S.; Henderson, G. M. (British Geological Survey, 2019)
The tables describe U-series chronology of speleothems in Ledyanaya Lenskaya and Botovskaya caves used in the manuscript "Paleoclimate evidence of vulnerable permafrost during times of low sea ice" by Vaks et al. 2020, Nature 577, 7789, 221–225. The information included in the tables is listed as following: Table 1: Table 1a includes U–Pb data from Ledyanaya Lenskaya and Botovskaya caves; Table 1b includes common Pb estimates for Ledyanaya Lenskaya and Botovskaya caves. Table 2: U–Th chronology of speleothems from Botovskaya Cave. The data shows when speleothems were growing in Ledyanaya Lenskaya Cave during the last 1.5 Ma and in Botovskaya Cave during the last 0.7 Ma. Speleothems grow when water seeps from the surface into the caves. If the soil and rock above the cave is permanently frozen, water will not reach the cave and speleothems will not grow. Together with the data from Vaks et al (2013) "Speleothems Reveal 500,000-Year History of Siberian Permafrost", Science 340, 6129, p 183–186, these speleothem deposition periods show when the permafrost above the two caves was discontinuous or absent. Published Paper: Vaks, A., Mason, A. J. Breitenbach, S. F. M., Kononov, A. M., Osinzev, A. V., Rosensaft, M., Borshevsky, A., Gutareva, O. S., Henderson, G. M. Palaeoclimate evidence of vulnerable permafrost during times of low sea ice. Nature 577, 7789, 221–225 (2020) doi:10.1038/s41586-019-1880-1